2004
DOI: 10.1002/biof.5520220161
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and physiological functions of polyphenols from apples

Abstract: Apples contain many kinds of polyphenols, and the main components are oligomeric procyanidins. Applephenon is apple polyphenol extract produced commercially from unripe apples, and has been used as food additive in order to prevent oxidation of components in foods and its application in functional foods is expected. In a lipid metabolism regulation study, administration of Applephenon has the potential to exert strong anti-oxidative activity and to inhibit consumption of vitamin E and anti-oxidative enzymes. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 5 publications
1
25
0
Order By: Relevance
“…Among the most important constituents of apple juice are polyphenolics that have the ability to increase its anti-oxidant potential. Polyphenolics also affect lipid methabolism (Akazone, 2004) and the absorption of cholesterol (Aprikian et al, 2001). Some authors have suggested that apple juice can reduce some forms of cancer (Barth et al, 2005); however, such an effect was only found for cloudy apple juice.…”
mentioning
confidence: 99%
“…Among the most important constituents of apple juice are polyphenolics that have the ability to increase its anti-oxidant potential. Polyphenolics also affect lipid methabolism (Akazone, 2004) and the absorption of cholesterol (Aprikian et al, 2001). Some authors have suggested that apple juice can reduce some forms of cancer (Barth et al, 2005); however, such an effect was only found for cloudy apple juice.…”
mentioning
confidence: 99%
“…IgE binds to mast cells, inducing the releases histamine, leukotriene and other cytokines involved in allergic inflammation (Turner and Kinet 1999;Galli et al 2008). It is known that some food components effectively suppress atopic symptoms, including eicosapentaenoic acid (EPA)/docosahexaenoic acid (DHA) (Yu and Bjorksten 1998;Hwang et al 2007) in fish oil, polyphenols (Akazome 2004), catechin (Noh et al 2008) and flavonoids (Theoharides et al 2004;Kawai et al 2007) in plants.…”
Section: Resultsmentioning
confidence: 98%
“…In recent years, anti-allergic foods utilizing the functionality of such food ingredients have been attracting attention, and lactic acid bacteria and plant polyphenols have been the main focus of reports. [2][3][4][5] We have studied the effective application of shochu distillery by-products (SDB) and have reported the effects of fermented barley extract (FBE), obtained from a barley-SDB, in preventing fatty liver induction by orotic acid and D-galactosamine-induced liver injury. 6,7) Additionally, oral administration of FBEP (the adsorbed fraction of FBE on the hydrophobic resin) in mice resulted in reduced oxidative stress by controlling glutathione-redox.…”
Section: Effects Of Single and Combined Administration Of Fermented Bmentioning
confidence: 99%